Permanent-magnet atom chips for the study of long, thin atom clouds - Llorente-Garcia, I; Sinclair, C; Curtis, E; Eriksson, S; Sauer, B; Hinds, E (2005)
Atom-chip technology can be used to confine atoms tightly using permanently magnetised videotape along with external magnetic fields. The one-dimensional (1D) gas regime can be realised and studied by trapping the atoms in high-aspect-ratio traps in which the radial motion of the system is confined to zero-point oscillation. © 2005 IOP Publishing Ltd.